Persepsi Mahasiswa Peserta SQI UNJ terhadap Efektivitas Metode Pembelajaran Tajwid - Khairunnisa Irmaliya; Aisyah Putri Santoso; Rafiq Alim Ramadhan; Habibi Ramadhan; Zulfatun Ni’mah (Yayasan Al-Afif, 2025)
This study addresses the gap between the objectives of Qur’anic recitation instruction and students’ actual mastery of tajwid rules in higher education. The research aims to examine students’ perceptions of the effectiveness of tajwid learning methods implemented in the Studi Qur’ani Intensif (SQI) program at Universitas Negeri Jakarta. A quantitative descriptive approach was employed, with data collected through a closed-ended questionnaire using a five-point Likert scale. The respondents consisted of 18 active SQI students at Tahsin levels 3 and 4, selected through purposive sampling. The findings indicate that the tajwid learning methods, supported by competent tutors, are perceived as highly effective, as reflected in improvements in makharijul huruf accuracy, sifatul huruf mastery, fluency, and automatic application of tajwid rules. The overall effectiveness score reached 87.78%, categorized as very effective. These results suggest that structured tajwid instruction significantly enhances students’ Qur’anic recitation skills and provides a strong foundation for improving instructional quality in Islamic higher education.